The new big book of U.S. presidents - Davis, Todd.; Frey, Marc (Marc E.) (Philadelphia : RP Classics, 2008)
Provides profiles of each United States president from George Washington to George W. Bush, with information on their lives, families, wives, and highlights of their time in office.
8.9
5-8
Keywords: Presidents -- United States -- Biography -- Juvenile literature; United States -- History -- Juvenile literature; Presidents -- United States; United States -- History; Presidents -- United States -- Biography; United States -- History